Kepadatan dan Estimasi Populasi Owa (Hylobates funereus) di Hutan Long Ayap, Kabupaten Berau, Provinsi Kalimantan Timur - Pamungkas, Ilham Hanaan Taqiuddin; Farajallah, Dyah Perwitasari; Entang Iskandar (Konservasi Hayati, 2024)
Gibbon (Hylobates funereus) is one of the endemic primates of Borneo Island. H. funereus is declared as endangered species in the IUCN Red List 2020. One of the threats is the loss of habitat caused by deforestation for palm oil plantations. The aim of the research is to assess population density and to estimate population of gibbons at Long Ayap Forest, Berau Regency, East Kalimantan Province. Observation is conducted using strip transect sampling method, carried out at three forest blocks at palm oil plantation of PT Mulia Inti Perkasa (MIP) from September to December 2022 with the total of 27 repetitions. The total gibbon population density is 11-11,96 individuals/km2. Estimation of gibbon population at Long Ayap Forest, Berau Regency, East Kalimantan Province is 17.82 individuals.